Implementation of lean manufacturing with the notion of quality improvement in electronics repair industry. (2021) - Samuel, R; Rajesh, M; Rajanna, S; Franklin, Emmanuel
Abstract: Electronic equipment repair services are one of the fastest-growing businesses that can create millions of jobs. But sensing its untapped potential, investments are flowing in creating a roadmap to improve its capacity to deliver quality products into the market. As far as electronics repair industries are concerned, there are bottlenecks and defects in each process. Moreover, due to the unprecedented crisis of COVID-19 has resulted in losing customers. To overcome these challenges, companies have to work to achieve their objectives other than profit. Industries have to adopt a better quality management system that addresses all industry areas, emphasizes customer satisfaction, and uses continuous improvement methods and tools. Lean manufacturing helps any organization to improve its efficiency, eliminate wastes, and achieve continuous improvements. This paper highlights the implementation of lean and quality tools for continuous improvements in electronic repair industries with no automation. Two levels of the repair bay process were chosen to remove the bottlenecks affecting quality and productivity. The paper sums up that implementing Lean Manufacturing resulted in continuous improvement and facilitated human workers to enhance their repair process quality.